Dynamics of Da'wah in Southeast Asia in the Digital Era - Maria, Suci Elsa; Zulhazmi, Abraham Zakky (UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
Recent developments in da'wah show positive and progressive dynamics, including in Southeast Asia. This condition is supported by the very massive growth of digital media. This article aims to analyze the dynamics of da'wah in Southeast Asia, especially in the digital era. As a region, Southeast Asia has its own characteristics, giving it a distinctive style of preaching. Southeast Asian people are known to be friendly, moderate and religiously tolerant. This research is descriptive qualitative research and library research. The conclusion of this research is that the potential of Islam in Southeast Asia is not merely a numerical power as the largest Muslim community, namely one-fifth of Muslims worldwide and its geopolitical strength. Furthermore, the roots of moderate and pluralistic Islamic life in Southeast Asia which have long historical roots have demonstrated the promising potential of this region. Da'wah in Southeast Asia should be the prototype of global da'wah. Da'wah in Southeast Asia has characteristics that are accommodative to local culture and anti-violence. Moderate and tolerant da'wah in Southeast Asia has reflected the teachings of the Koran and the teachings of the Prophet, and has proven effective in inculcating Islamic values in society at large.